A Study on the Awareness Level of Academicians on Small Saving Schemes in Tamil Nadu - Kasilingam, R.; Jayabal, G. (Indian Journal of Finance, 2009)
The very word awareness refers to a stage at which one’s mind becomes conscious of the existence of a particular truth, event or object. Hence, awareness is a course of action, by which, one becomes familiar with the existence of a new thing. However, he may not have a thorough knowledge of that thing. Acquiring the knowledge of the latest developments in a particular field also amounts to awareness; hence, awareness is a continuous process. In this study, the term awareness is used to describe the awareness of investors about the existence of numerous avenues of savings and investments. Acquiring knowledge about a variety of investment channels facilitates the investor to compare the merits and demerits of each. Many good schemes and good products have failed due to low awareness level among people. Hence, it is necessary for the agencies promoting saving schemes to know present level of awareness among people. They should also know the factors that determine the awareness level of investors to design suitable promotion schemes.